Utilizing Animated Video to Improve Public Information Dissemination in Pangandaran Regency - vany octaviany; Liestyowati; Ganjar Mohamad Disastra; Neng Ratna; Ekin Surbekti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Pangandaran Regency is one of the leading tourism destinations in West Java that requires strengthened public communication, particularly in delivering environmental cleanliness education to stakeholders. Conventional media remains less effective in reaching all segments of society, creating the need for more innovative communication media. This community service activity was carried out in collaboration with the Office of Communication, Informatics, Statistics, and Encryption (Diskominfo) of Pangandaran Regency by utilizing animated video as a medium for delivering public information regarding the importance of maintaining cleanliness in tourism destination areas. The implementation method consisted of a needs survey and discussion, concept and script development, animated video production, dissemination through government digital channels and social media, as well as evaluation of the effectiveness of the developed media. The results of the activity indicate that animated video is able to deliver cleanliness-related messages in a more engaging, understandable, and interactive way compared to conventional media. This medium not only functions as a tool for delivering information but also serves as a means to build awareness and increase the participation of tourism actors, such as hotel managers, restaurant owners, traders, tour guides, and tourists themselves, in maintaining cleanliness and the sustainability of the tourism environment.